p53 Expression in Colorectal Carcinoma in relation to Histopathological Features in Ugandan Patients - Rambau, Peter F.; Odida, Michael; Wabinga, Henry (African health sciences, 2008)
It has been shown that colorectal carcinoma is increasing in incidence in African countries. This could be due to change in life style. Molecular pathogenesis of colorectal cancer commonly involves mutation in p53 gene which leads to expression of p53 protein in tumor cells. Expression of p53 protein has been associated with poor clinical outcome and reduced survival in patients. This was a retrospective laboratory based study carried out in the Department of Pathology Makerere University, Kampala, Uganda. The aim of the study was to evaluate the expression of p53 protein in colorectal carcinoma in Ugandan patients, specifically its association with histological types, degree of differentiation, sites of the tumor and demographic characteristics of the patients. Immunohistochemistry was carried out on 109 patient\'s paraffin embedded tissue blocks of colorectal carcinoma diagnosed in the Pathology Department, Faculty of Medicine Makerere University Kampala during the period 1995 to 2005. The indirect immunoperoxidase method using monoclonal antibody p53 DO-7 and Envision + Dual link system-HRP to detect p53 expression was used. Haematoxylin and eosin stain was used for evaluation of histological types and degree of differentiation of the tumors. Topography of the tumors and demographic data were obtained from accompanying histological request forms. Out of 109 patient\'s tissue blocks that were studied, 61 cases (56%) expressed p53 protein in the nucleus of malignant cells. Right sided colonic tumors were commoner (53.2%) than left sided colonic tumors (46.8%). p53 protein was expressed more in left sided colonic tumors with a significant difference (p<0.05), it was also expressed more in well differentiated tumors and non mucinous adenocarcinomas but with no significant difference (p>0.05). p53 expression was not affected by age or sex. Frequency of p53 protein expression in Ugandan patients did not differ from that reported in the other parts of the world. It was expressed more in the left sided colonic tumors and this could support the hypothesis that right and left colonic tumors could have different pathogenesis and probably also responsible for difference in prognosis in these two topographic sites.
Keywords: p53; colorectal carcinoma; Immunohistochemistry